PENGARUH PERLAKUAN KOSENTRASI BIOURINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT ( Ipomoea reptans Poir) - Albinus Ngapu; I Dewa Nyoman Raka; Farida Hanum (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
Research entitled the effect of cow biourine concentration treatment on yield and growth of ground kale plants (Ipomea reptans Poir) Determine the effect of beef biourine concentration treatment on growth and yield of ground kale plants (Ipomoea reptans Poir), Biourine concentration treatment what is the best cow for the growth and yield of ground water spinach plants (Ipomoea reptans Poir) .This study used a Randomized Block Design (RBD), if the treatment had a significant effect with the LSD level of 5% to find out the best effect of each treatment. that the effect of cow biourine treatment has a very significant effect on all observed water spinach parameters.The effect of 500 ml / 1 liter water biourine concentration treatment results in other observed parameter values ​​such as highest plant height (B5 = 46.75 cm), highest number of leaves ( B5 = 45.00 cm) The highest leaf area (B5 = 991.92 cm2), total fresh weight 16.57 g).